Avaliação do risco de doença cardiovascular em indivíduos assintomáticos com periodontite severa de uma população rural - Londero, Ananda Barrachini (2024)
Cardiovascular diseases (CVD) are non-communicable diseases and are responsible for most of the causes of death in the world. Periodontitis is also a non-communicable disease that has a high prevalence in the population. Both CVD and periodontitis may reflect social inequality. The study of the pathophysiology of these diseases has shown that through inflammatory mechanisms may there is an interaction between these diseases. The aim of this study is to evaluate the association between severe periodontitis (stage III/IV) and the risk of developing cardiovascular disease in asymptomatic patients for cardiovascular disease using the Framingham Score. Furthermore, considering the impact of periodontal inflammation on blood pressure, our aim was also to evaluate the association between gingival bleeding and systolic blood pressure. This is a cross-sectional study that is a secondary data analysis, based on data from a representative sample of the rural area of the city of Rosario do Sul / Rio Grande do Sul. For the analyses in this study, 429 individuals were eligible, with a mean age of 49.4 years. 77.4% of subjects have periodontitis stage III/IV. Most subjects are overweight, high blood pressure and have medium or high risk of developing cardiovascular disease. After adjusted analysis, severe periodontitis remained significantly associated with the Framingham Score, increasing the cardiovascular risk of this population by 40%. It was observed that SS > 10% was significantly associated with higher levels of systolic blood pressure.